Identifikasi Bahan Tambahan Makanan (BTM) Berupa Formalin, Boraks, Pewarna Rhodamine-B Pada Makanan Di Pasar Atas Cimahi - Ramadhan Putra, Husni; Dwi Frastika, Elfa; Hasanah, Nurul; Azzizatun Nisa, Nur; Thalia Syalsabila, Vinka; Nur Asriyah, Aas; Dewi, Rahmalia (JURNAL KESEHATAN KARTIKA, 2023)
The level of poisoning in Indonesia is increasing. Food is one of the contributors to the cause of some people experiencing poisoning. Food Additives (BTP), which are prohibited from being used by the government, are often violated by rogue elements who want to make more profit. Low prices and easy access are one of the reasons why people are tempted to commit fraud against their merchandise. This review describes several types of BTP that are often abused by some rogue traders with very bad effects in the short term or slow. Prohibited food additives that are often used by traders are formalin, borax and rhodamine B. Consumption in excess levels will cause digestive disorders, respiratory disorders, central nervous disorders, cancer and even death. To stop distribution continuously, there must be a stop and testing by the authorities.